Identification of a family of cAMP response element-binding protein coactivators by genome-scale functional analysis in mammalian cells - Vadim Iourgenko; Wenjun Zhang; Craig Mickanin; Ira Daly; Can Jiang; J. Mark Hexham; Anthony P. Orth; Loren Miraglia; Jodi Meltzer; Dan Garza; Gung‐Wei Chirn; Elizabeth McWhinnie; et al. (2003)
This report describes an unbiased method for systematically determining gene function in mammalian cells. A total of 20,704 predicted human full-length cDNAs were tested for induction of the IL-8 promoter. A number of genes, including those for cytokines, receptors, adapters, kinases, and transcription factors, were identified that induced the IL-8 promoter through known regulatory sites. Proteins that acted through a cooperative interaction between an AP-1 and an unrecognized cAMP response element (CRE)-like site were also identified. A protein, termed transducer of regulated cAMP response element-binding protein (CREB) (TORC1), was identified that activated expression through the variant CRE and consensus CRE sites. TORC1 potently induced known CREB1 target genes, bound CREB1, and activated expression through a potent transcription activation domain. A functional Drosophila TORC gene was also identified. Thus, TORCs represent a family of highly conserved CREB coactivators that may control the potency and specificity of CRE-mediated responses.